Сек’юретизація як ефективна складова управління фінансовими ресурсами аграрного підприємства в умовах війни - Халатур, Світлана Миколаївна; Khalatur, Svitlana; Сірко, Анна Юріївна; Sirko, Anna; Малоок, Анастасія; Malook, Anastasi (Дніпровський державний технічний університет, 2024)
Авторами статті розглянуто процес управління фінансовими ресурсами аграрних підприємств, а також приділено увагу дослідженню сек’юретиації як ефективної його складової. В статті досліджено , що використовуючи певні інструменти механізму диверсифікації активів аграрні підприємства здатні покращити ефективність фінансової та інвестиційної діяльності, забезпечуючи при цьому його фінансову стійкість, дохідність та прибутковість на достатньому рівні. Доведено, що сек’юритизація виступає дієвим фінансовим механізмом, за допомогою якого підприємства можуть перетворювати свої активи (наприклад, дебіторську заборгованість чи майбутні грошові потоки) на цінні папери, які продаються інвесторам для залучення фінансових ресурсів. В умовах війни, коли аграрні підприємства стикаються зі зменшенням доступу до традиційних джерел фінансування, сек’юретизація може стати важливим інструментом для забезпечення ліквідності та фінансової стабільності. The authors considered the process of managing financial resources of agricultural enterprises, and also paid attention to the study of securitization as an effective component of it. The article examines that using certain tools of the asset diversification mechanism, agricultural enterprises are able to improve the efficiency of financial and investment activities, while ensuring its financial stability, profitability and profitability at a sufficient level. Securitization has been proven to be an effective financial mechanism by which companies can convert their assets (such as receivables or future cash flows) into securities that are sold to investors to raise financial resources. In times of war, when agricultural enterprises face reduced access to traditional sources of financing, securitization can become an important tool for ensuring liquidity and financial stability. Securitization is an effective financial tool for agricultural enterprises, especially in times of war, when it is necessary to maintain liquidity and maintain operational activities in conditions of limited resources. It allows you to effectively attract financing, minimize risks and ensure the sustainability of the enterprise. Thanks to international initiatives and state support, this mechanism can become a key element of the financial strategy of the agricultural sector in the crisis period. Protection of agrarian enterprises from systemic risks is a key component of ensuring their stability and development in conditions of instability. A comprehensive approach to their forecasting and minimization allows agrarian enterprises not only to withstand difficult conditions, but also to ensure sustainable growth in the long term. Hence, securitization is a powerful risk management mechanism that helps businesses increase liquidity, minimize financial risks and diversify capital sources. Its implementation makes it possible to ensure business stability in a changing market environment, increase attractiveness for investors and strengthen the company's financial stability. This tool is becoming an important component of the modern approach to risk management, especially in difficult economic conditions.
Securitization as an effective component management of the financial resources of an agricultural enterprise in the conditions of war
Keywords: фінансові ресурси; financial resources; управління фінансовими ресурсами; management of financial resources; сек’юретизація; securitization; аграрні підприємства; agricultural enterprises